In sight : my life in science and biotech - Levy, Julia G., 1934- (University of Toronto Press, 2020)
"In Sight is a memoir about how a love of science and discovery drove Julia Levy, a celebrated scholar and biotech CEO, to work her way through gender bias in order to achieve academic and professional recognition. Her story traces the unconventional invention of a breakthrough drug treatment from its development from laboratory researchin the laboratory to its application as a medical treatment for vision loss. Told from a female perspective, In Sight is a unique and personal story covering Levy's early years as a refugee, her university training in the UK, and her appointment as professor at the University of British Columbia. Years spent as an academic led gave the author to unexpected exposure to the biotechnology industry and a chance meeting with colleagues that led to the formation of a lucrative biotechnology company, known today as QLT Inc. The bulk of the book covers the years spent building the company, and Levy's surprising transition from chief scientific officer to CEO. In Sight is an honest description of the trials of drug development, the tensions inherent in the commercialization of health innovations, and the truly remarkable hurdles faced by women in the scientific community."--